(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
As far as the site I of Dadibadi is concerned, its underground water shows marked variation in SEM and SU. Hence, from Dadibadi, the maximum range of arsenic concentration was observed from site I i.e. 0.02-0.10, while the minimum range of arsenic concentration was observed from site 6 i.e. 0.005-0.025 mg/l. The highest value of mean arsenic concentration was observed from site 2 i.e. 0.04578 mg/l while the lowest mean arsenic concentration was observed from site 6 and the value was 0.00979 mg/l. Similarly the minimum SD observed from the site 6 i.e. 0.00886 while the maximum SD was 0.03378 from site 3.